Automação residencial com arduino - Silva, Jander Couto da (2022)
This work aims to propose the development of a home automation system using the Arduino platform applied for lighting and irrigation of two points of a small garden. For this work, a bibliographic research was carried out on the subject of home automation with Arduino and on some of the main possibilities of sensor, actuator and communication modules for this use, after deepening the study and analysis, the two agents were proposed. In the next step, the components and the input and output modules were defined. For the automation of lighting via Bluetooth, a specific application was chosen, and then the programming code was developed for each situation. And for the demonstration of the system, a prototype was developed on a reduced scale and a floor plan for the location of the components in the residence was defined. The tests performed presented the expected result according to the program. It is concluded that the Arduino and its modules emerge as a simple, versatile and low-cost alternative for punctual home automation.